Surface modification of aluminium alloy 5052 and its corrosion characterization / Abu Hanifah Muhamad Ali - Abu Hanifah, Muhamad Ali (2018)
Aluminum (Al) casting alloys are important materials for the fabrication of engine components such as engine block, pistons and cylinder head. In the present study, a self-organized nanostructured Al2O3 layer on AA5052 H32 series was fabricated and followed by heat treated at 450 °C for 1.5 h. The microstructural features and corrosion characterization was the interest part to study. In addition, mechanical and corrosion behavior of Al2O3 nanoporous after anodizing and heat treatment were investigated. From the microstructural point of view, the average length and diameter of the optimized nanoporous arrays ranged from 0.5 μm and 20 nm. Scratch test conducted to nanoporous layer and reveal that scratch hardness of heat treated AA5052 is 15.32 MN/m², higher than anodized sample 9.68 MN/m². Besides, anodization increase the hardness of AA 5052 from 50.5 HV to 85.3HV. Then, it being enhanced by heat treatment process and reduce to 60.7. Besides, the heat treated nanoporous layer show the hydrophilic properties where water contact angle value is only 13.7°. The results of corrosion tests in artificial sea water (ASW) showed that the corrosion rate values significantly decreased from after anodization and subsequent heat treatment compared to the substrate. Specifically, anodized sample corrosion protection improved 40.08% and while heat treated sample improved 88.17% from AA 5052 bare substrate.